A proposed Atmospheric Hazards Early Warning System (AHEWS) incorporated in the new structure of the Greek Regional Administration 'Kallikratis' - Nastos, P. T.; Matsangouras, I. T. (Georisk, 2013)
Natural hazards pose an increasing threat to society and, for this reason, it is necessary to develop models and methodologies for better understanding and forecasting extreme weather events. A new structure of the Greek Regional Administration (Kallikratis) was established in 2011, based on geographical criteria, in order to create an operational and capable administration. An Atmospheric Hazards Early Warning System (AHEWS) could be characterised as an ultimate tool for the local authorities (first and second tier level) in order to organise and implement efficient plans to mitigate the risk. New operation centres (related to regional and municipality administration level) are suggested to be staffed and equipped with the proposed Early Warning System (EWS). The AHEWS will link to extensive Geographical Information Systems (GIS) datasets and methodologies for safety plans by government agencies and services in order to mitigate the impacts caused by atmospheric extreme events. AHEWS involves high-resolution Numerical Weather Prediction (NWP) products, ground observation network, lightning detection network and satellite information in terms of early convective, initiation and Now-Casting. Storms, lightings, gale winds, snow, hail, tornadoes, low temperatures, heatwaves and several others extreme events are weather phenomena that AHEWS deals with in order to prevent and mitigate impacts on humans and constructions. An automated dissemination procedure is described here for individual and administrative users, followed by safety and action plans, respectively. © 2013 Taylor & Francis.
Keywords: action plan; Administration; atmospheric hazard; early warning system; extreme event; GIS; Greece; hazard assessment; implementation process; Kallikratis; Kapodistrias; mitigation; nowcasting; numerical model; safety; weather forecasting